The effect of aerobic exercise in reducing the effects of psychological and occupational stress for women of all ages (25 - 45) years old (Journal of the College of Basic Education, 2022)
Aerobic exercises work in general, and in particular aerobic exercises that combine body strength and movement flexibility and work to maintain cardiovascular fitness and because they are exercises accompanying music that raise morale and stimulate individuals in general and relieve stress and psychological pressure that are exposed to as a result of life's demands and difficulties. Women face many difficult and unwanted situations in their social and professional life that endanger their well-being, as life and its pressing demands generate physical and psychological disturbances. Therefore, the researcher undertook this study to find out the extent of the impact of aerobic exercise in reducing the effects of psychological stress and professional pressure on a sample. search.As for the research problem, it lies in the fact that psychological stress is one of the diseases of the age and its problems that have the largest role in causing many health and psychological diseases, and here comes the role of exercises in increasing self-confidence and relaxation and getting rid of symptoms associated with depression and anxiety in addition to mood swings that cause many problems. As for the objectives of the research, they were to identify the percentage of psychological and occupational stress on the research sample and to identify the extent of the effect of aerobic exercises in alleviating the effects of psychological and professional pressures on the research sample. The experimental approach with two equal groups, experimental and control was used. The research sample was (36) non-mathematical women workers in various professions.The results have proven the superiority of the post-test results for the two groups and the presence of significant differences between the post-test results of the two groups in the results of psychological stress and occupational stress in favor of the experimental group, and it is one of the most important findings of the research. As for the recommendations, the researcher recommended conducting similar studies on samples of different ages of males and females and conducting a study comparing exercises Aerobics and zumba exercises, and to know their impact on the psychological state.